MAKING LAND MANAGEMENT MORE SUSTAINABLE: EXPERIENCE IMPLEMENTING A NEW METHODOLOGICAL FRAMEWORK IN BOTSWANA. (14th September 2011) - Perkins, J.; Reed, M.; Akanyang, L.; Atlhopheng, J.; Chanda, R.; Magole, L.; Mphinyane, W.; Mulale, K.; Sebego, R.; Fleskens, L.; Irvine, B.; Kirkby, M.
ABSTRACT It is increasingly recognised that tackling land degradation through more sustainable land management depends on incorporating multiple perspectives by using a variety of methods at multiple scales, including the perspectives of those who manage and/or use the land. This paper reports experience implementing a previously proposed methodological framework that is designed to facilitate knowledge sharing between researchers and stakeholders about land degradation severity and extent, and sustainable land management options. Empirical findings are presented from the Botswana site of the EU‐funded Desertification Mitigation and Remediation of Land project. The paper reflects upon the challenges and benefits of the proposed framework and identifies a number of benefits, notably related to insights arising from the integration of local and scientific knowledge, and the ownership of the sustainable land management strategies that emerged from the process. However, implementing the framework was not without challenges, and levels of poverty and formal education may limit the implementation of the framework in some developing world contexts. Copyright © 2011 John Wiley & Sons, Ltd.